"The Government Believes That History Unfolds as History Unfolds" In what ways have consecutive Dutch governments sought to address Dutch violence during Indonesia's independence war of 1945-1949? A study into the approaches applied by Dutch governments over the course of almost seventy years - Assies, Tessa (Department of Political Studies, 2020)
Since the end of the twentieth century, more and more countries have been confronted with how to deal with injustice from the past. Current governments are increasingly asked requested to assume accountability for crimes committed by their predecessors. Due to the growth of human rights, the discussion surrounding this, a more conscious society and the empowerment of victims, old cases are increasingly being exposed. This is also the case for the Dutch government. During the war of independence in Indonesia between 1945 and 1949, the population of this country fought to be released from under the Dutch rule. Later research would show that the Dutch army committed crimes there under the guise of 'an internal mission' to preserve the colony for the kingdom. After the war, it remained undiscussed, and successive Dutch governments even actively 'neutralised' the case. Later, when a clearly defined group of victims emerged, the Dutch government had to deal with it differently. In the spirit of the global developments concerning human rights and interest in history, the Dutch government took some tentative steps in addressing the Indonesian issue. Real changes however were enforced through a lawsuit filed by the aforementioned group of victims. These victims won their case, and the ruling established for the first time that the Dutch state had a responsibility towards the group of victims from Indonesia. Did this lead to a change in the Dutch governmental approach towards the Dutch violence during the independence war? Has anything actually changed over the years to this approach? This thesis examines the attitude and approach of successive Dutch authorities towards Dutch violence in Indonesia, divided over three periods: the five-decades post-war; the period 1995-2011 (in this last year the lawsuit was filed); and the time post-lawsuit.